PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN PROYEK JASA KONSTRUKSI - Tunggul Barita Parulian; Sawarni Hasibuan (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
This research aims at analyzing the influence of the leadership, corporate culture, job satisfaction toward employee job satisfaction, and their impact to the employee performance. The proposed hypotheses of this research: H1, to test the relationship between of the variable leadership with the variable culture organization. H2, to test the relationship between of the variable leadership with the variabel job satisfaction. H3, to test the relationship between of the variable culture organisation with the variabel job satisfaction. H4, to test the relationship between of the variable culture organisation with the variabel employee performance. H5, to test the relationship between of the variable leadership with the variabel employee performance. H6, to test the relationship between of the variable job satisfaction with the variabel employee performance.  The result of this research: H3, the variable culture organization have influence positive and significance with the variable job satisfaction. H5, the variable leadership have influence positive and significance with the variable employee performance. H6, job satisfaction have influence positive and significance with the variable employee performance.